Effect of Using an Inclined-Pole Method on the Practice of an Alpine Ski Race - SANADA, Daisuke; KOBAYASHI, Toru; BAN, Yoshihiko (Journal of Ski Science, 2004)
The purpose of this study was to clarify the effect of using an Inclined-Pole Method on the practice of an Alpine ski race. The subjects of the race were 8 junior racers (ages 14.6±1.9). They performed slalom test runs seven times that were composed of 8.6 meters of intervals, 1.5 meters of shaking width (offset). The first, second, sixth and seventh runs were set in the usual way with Upright-Poles. From the third to the fifth runs, the Inclined-Pole Method was set up that put the flex poles at an inclination of 20 degrees to the side by which the racers pass. A digital video camera was set up at the front of the subjects. The angle variance of the skiers' lower legs and the time between the 8th gate and the 13th gate were analyzed from the above video images. The results of this study were as follows: 1) The time that many subjects had taken was shorter using the Inclined-Pole Method than that of the Upright-Pole Method. 2) From analyzing the angle variance of the skiers' lower legs between the gate and the next gate, the switch timing of right to left turns (or left turn to right) were faster using the Inclined-Poles in many cases. These results suggest that the Inclined-Pole method has a positive effect on making more effective timings of switching turns.